Comparative effect of allopolyploidy on transposable element composition and gene expression between Gossypium hirsutum and its two diploid progenitors. Issue 1 (20th January 2019) - Cheng, Hua; Sun, Gaofei; He, Shoupu; Gong, Wenfang; Peng, Zhen; Wang, Ruiping; Lin, Zhongxu; Du, Xiongming
Abstract: An allopolyploidization event formed allotetraploid Gossypium species from an A‐genome diploid species and a D‐genome diploid species. To explore the responses of transposable elements (TEs) to allopolyploidy, we assembled parallel TE datasets from G. hirsutum, G. arboreum and G. raimondii and analyzed the TE types and the effects of TEs on orthologous gene expression in the three Gossypium genomes. Gypsy was the most abundant TE type and most TEs were located ∼500 bp from genes in all three genomes. In G. hirsutum, 35.6% of genes harbored TE insertions, whereas insertions were more frequent in G. arboreum and G. raimondii . G. hirsutum had the highest proportion of uniquely matching 24‐nt small interfering RNAs (siRNAs) that targeted TEs. TEs, particularly those targeted by 24‐nt siRNAs, were associated with reduced gene expression, but the effect of TEs on orthologous gene expression varied substantially among species. Orthologous gene expression levels in G. hirsutum were intermediate between those of G. arboreum and G. raimondii, which did not experience TE expansion or reduction resulting from allopolyploidization. This study underscores the diversity of TEs co‐opted by host genes and provides insights into the roles of TEs in regulating gene expression in Gossypium . Abstract : No large‐scale burst of transposable elements (TEs) activity was detected in Gossypium hirsutum after allopolyploidy. More TEs were silenced by 24‐nt siRNAs in G. hirsutum than in two diploid progenitors. The effects of TEs on gene expression varied substantially among species, implicating the multiple roles of TEs in the genome of Gossypium .